Frequency of Hypocalcemia after Total Thyroidectomy: A Clinical Study - Mehmood, Tariq; Imran Anwar, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Hypocalcaemia is the most frequent complication following total thyroidectomy, resulting from parathyroid gland injury or devascularization. It can cause transient or permanent metabolic disturbances, requiring close monitoring and intervention. The burden of hypocalcaemia is particularly relevant in Pakistan due to prevalent nutritional deficiencies and variations in surgical expertise. Objective: To determine the frequency of hypocalcaemia following total thyroidectomy and assess its association with age and gender in a tertiary care hospital in Pakistan. Methods: This descriptive case series was conducted at the Department of General Surgery and Surgical Oncology, Sheikh Zayed Hospital, Lahore, from December 16, 2024, to May 15, 2025. A total of 88 patients undergoing total thyroidectomy were included through consecutive non-probability sampling. Patients with recurrent thyroid swelling or preoperative hypocalcaemia were excluded. Serum calcium levels were measured preoperatively, 24 and 48 hours postoperatively, and on the fifth postoperative day. Hypocalcaemia was a corrected serum calcium level <2.1 mmol/L within five days post-surgery. Data were analyzed using SPSS version 20.0, with a chi-square test applied for associations; p ≤ 0.05 was considered significant. Results: The mean age of participants was 42.6 ± 11.8 years (range 19–68), with a female predominance (75%). The average thyroid swelling size was 5.2 ± 1.6 cm. Mean serum calcium declined significantly postoperatively: 2.34 ± 0.12 mmol/L preoperatively, 2.05 ± 0.18 mmol/L at 24 hours, and 2.00 ± 0.21 mmol/L at 48 hours, followed by partial recovery on the fifth day (2.07 ± 0.16 mmol/L). Overall, 30 patients (34.1%) developed hypocalcaemia. No significant association was found between hypocalcaemia and age (p = 0.98) or gender (p = 0.47). Conclusion: Hypocalcaemia was observed in nearly one-third of patients following total thyroidectomy, with no significant influence of age or gender. These findings highlight the need for routine postoperative calcium monitoring, patient counseling, and early supplementation to minimize morbidity. Preoperative correction of nutritional deficiencies and standardized surgical protocols are essential to improve outcomes in the Pakistani context.